Fraud Hexagon: Detection of Fraud of Financial Report in State-owned Enterprises in Indonesia - Sudrajat, Sudrajat; Suryadnyana, Nyoman Adhi; Supriadi, Taufiq (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2023)
This study aims to identify the potential for fraudulent financial reporting using the Fraud Hexagon approach with pressure, capability, collusion, opportunity, rationalization, and ego indicators. The population in this study is state-owned companies with observations for 12 years, from 2010 to 2021, and uses regression analysis with SPSS tools to test the Hypothesis. The results showed that pressure and ego could detect the potential for fraudulent financial reporting. There is a tendency for management to report conditions that are different from the actual conditions when under pressure in the form of performance targets that are not supported by the resources they have. CEO duality also provides an excellent opportunity for fraudulent financial reporting practices because when there is a  position war, there is no cross-check between departments, so other parts cannot detect the potential fraud committed by the CEO. This condition also indicates weak control processes that provide wider opportunities for fraudulent financial reporting. At the same time, variables of ability, collusion, opportunity, and rationalization cannot detect financial statement fraud. This condition is because state-owned companies are required to implement the Minister of Finance Regulation number PER-11/MBU/07/2021 and the Financial Services Authority number 13/POJK.03/2017 as the basis for the implementation of Good Corporate Governance so that it is possible to commit financial reporting fraud very small.